Neuromodulator and Emotion Biomarker for Stress Induced Mental Disorders. (14th March 2016) - Gu, Simeng; Wang, Wei; Wang, Fushun; Huang, Jason H.
Abstract : Affective disorders are a leading cause of disabilities worldwide, and the etiology of these many affective disorders such as depression and posttraumatic stress disorder is due to hormone changes, which includes hypothalamus-pituitary-adrenal axis in the peripheral nervous system and neuromodulators in the central nervous system. Consistent with pharmacological studies indicating that medical treatment acts by increasing the concentration of catecholamine, the locus coeruleus (LC)/norepinephrine (NE) system is regarded as a critical part of the central "stress circuitry, " whose major function is to induce "fight or flight" behavior and fear and anger emotion. Despite the intensive studies, there is still controversy about NE with fear and anger. For example, the rats with LC ablation were more reluctant to leave a familiar place and took longer to consume the food pellets in an unfamiliar place (neophobia, i.e., fear in response to novelty). The reason for this discrepancy might be that NE is not only for flight (fear), but also for fight (anger). Here, we try to review recent literatures about NE with stress induced emotions and their relations with mental disorders. We propose that stress induced NE release can induce both fear and anger. "Adrenaline rush or norepinephrine rush" and fear and anger emotion might act as biomarkers for mental disorders.